Analisis beberapa faktor dominan yang mempengaruhi perilaku adopsi inovasi pelaku industri kreatif sub sulaman khas Minang Kabau - Sari, Mareta Kemala; Amaluis, Dina; Saputra, Syailendra Eka (Jurnal Kajian Manajemen Bisnis, 2018)
This study aims to prove empirically the influence of the resources used, creativity and courage to face risks towards the innovative adoption of Minang Kabau craftsmanship of handicraft sub-craftsmanship. In this study all 467 people from West Sumatra typical craftsmen were sampled. . The analysis model used in this study is simple regression which is processed using the STATA program assistance. Based on the results of the tests that have been conducted it was found that the resources possessed, business creativity, and courage to face risks influence the adoption of innovations of Minang Kabau's unique sub-embroidery business actors.Keywords: Adopsi inovasi; sumber daya; kreatifitas; keberanian menghadapi risiko